A Combination of Single Nucleotide Polymorphisms is Associated with the Interindividual Variability of Cholesterol Bioavailability in Healthy Adult Males. Issue 22 (15th October 2020) - Desmarchelier, Charles; Wolff, Estelle; Defoort, Catherine; Nowicki, Marion; Morange, Pierre‐Emmanuel; Alessi, Marie‐Christine; Valéro, René; Nicolay, Alain; Lairon, Denis; Borel, Patrick
Abstract : Scope: Cholesterol bioavailability displays a high interindividual variability, partly due to genetic factors. Existing studies have focused on single nucleotide polymorphisms (SNPs) analyzed individually, which only explained a minor fraction of the variability of this complex phenotype. The aim is to identify a combination of SNPs associated with a significant part of the variability in cholesterol bioavailability. Methods and results: Thirty‐nine healthy adult males are given a standard test snack containing 80 mg heptadeuterated (D7) cholesterol. The plasma D7‐cholesterol concentration is measured at equilibrium 40 h after test snack intake. The D7‐cholesterol response (D7‐cholesterol/total cholesterol concentration) exhibits a relatively high interindividual variability (CV = 32%). The association of exonic SNPs in candidate genes (188 genes involved in or related to cholesterol metabolism) with the plasma D7‐cholesterol response is assessed by univariate statistics followed by partial least squares regression. A significant model ( p ‐value after cross‐validation ANOVA = 1.64 × 10 −7 ) that includes 8 SNPs ( SOAT2 ‐rs9658625, DNAH11 ‐rs11768670, LIPC ‐rs690, MVK ‐rs2287218, GPAM ‐rs10787428, APOE ‐rs7412, CBS ‐rs234706, and WRN ‐rs1801196) explains 59.7% of the variance in cholesterol bioavailability (adjusted R ²). Conclusion: Here a combination of SNPs is significantly associated with the variability in dietary cholesterol bioavailability in healthy adult males. Abstract : Cholesterol bioavailability displays a high interindividual variability, partly due to genetic factors. The authors perform an acute cholesterol‐feeding experiment in 39 healthy normolipemic participants who consumed a test snack providing 80 mg cholesterol as heptadeuterated cholesterol. Using a multivariate statistical approach, the authors find that a combination of 8 exonic SNPs is significantly associated with the interindividual variability in cholesterol bioavailability (adjusted R ² = 0.597).